How Employee Engagement and Career Management Affect Employee Turnover: Insights from an Educational Institution - Theresia Nona Ega; Nazwa Hamidah Ali (DPPM Universitas Pelita Bangsa, 2025)
This study aims to analyze the influence of employee involvement and career management on the level of employee turnover in an organization. The research was conducted at the ASISI Jakarta High School educational institution using a survey method using a questionnaire distributed to 32 respondents. Data analysis was performed using SmartPLS 4 to ensure the robustness of the findings. The results show that Career Management has a positive and significant influence on Employee Turnover, Employee Engagement has a positive and significant influence on Career Management, and Employee Engagement does not have a significant influence on Employee Turnover. This study provides important insights for management in developing strategies to reduce employee turnover rates by implementing structured career management programs and enhancing employee engagement initiatives. Additionally, this research suggests that future studies explore other potential mediating factors influencing employee turnover in different organizational contexts.